The Effect Cytokinin Aplication and Kosarmas Fertilizer on Rice Seed Filling Impari Sembilan in Pintupadang. - Jumaria Nasution; Silitonga, Romaya Sitha (Talenta Publisher, 2020)
Impari Sembilan is one of the superior varieties used in Pintupadang. This seedling is one of the superior varieties produced from an agricultural hall in Indonesia. Rice productivity efforts can be increased by using superior varieties administration of growth regulators. Cytokines application a role in the formation of grains and root during the initial process of grains development, affect the percentage of seed and will affect the yield. kosarmas fertilizer is an organic fertilizer from cow dung, charcoal, candlenut shell and golden snails as organic fertilizer which improves soil physic. The purpose of the study was to evaluate the effect of cytokynins and KOSARMAS fertilizer on wet weight, dry weight, seed filling of Impari rice plants. This study used a completely randomized design with two factors, namely the cytokinin concentration of 0,10,25,50 ppm and Kosarmas liquid fertilizer concentration of 0,20,30,50 ml. Based on the analysis of error variance of 5%. Cytokinin at a concentration of 50 ppm increased the height of Impari rice stalks while cytokinin applied at a concentration of 25 ppm increased, the amount of fresh weight of 100 rice seed, dry weight of sed. A dose of 30 ml kosarmas fertilizer increases the total amount of panicle grain. REFERENCES Daie, J.1985.Carbohydrate partitioning and metabolism in crops.Hort.Review,7: 69-108. Gomez, K. A., And Gomez, A. A. 1976. Statistical Procedure For Agriculture Research With Emphasize On Rice. International Rice Research Institue, Los Banos Philipines Mukarim ,A. K. 2005. Peupukan berimbang pada tanaman pangan khusus padi sawah : Seminar Rutin Pulitbang Tanaman Pangan. Bogor. Ookura, T.Wada, M.Sakakakibara, Y.Jeong,K.H.Maruta, I.Kawamaru,Y and Kasamo,K.1994. Indentifacition and characterization of family of gene for the plasma membrane H+-ATP ase Oryza sativa L. Plant cell Physiol.,35:1251-1256. Oparka, K.J, and Gates ,. P.J.1981. Transport Of assimilates in the developing caryopsis of rice. Ultrastructure of the pericarp vascular bundle and its connection with the aleurone layer. Planta,151:561-573. Shah, S.H.2006.The response of nigella Sativa L.to foliar application of gibberellic acid and kinetin.Biol.Plant.In Press. Taize and Zeiger. 2002. Plant Physiology Third Edition. Sinauer Association: USA.